Experimental and numerical study on reinforced concrete beam-column joints with diagonal bars: Effects of bonding condition and diameter. (March 2022) - Shen, Xinyu; Li, Bo; Chen, Yung-Tsang; Tizani, Walid
Abstract: Diagonal bars anchored in beams have been proven to be an effective reinforcement detail for reinforced concrete interior beam-column joints (BCJs) in mitigating the congestion of conventional stirrups without compromising their seismic performance. This paper investigates the effects of bonding condition and diameter of diagonal bars on the seismic performance of interior BCJs. Four interior BCJ specimens, including one control specimen reinforced with conventional stirrups and three others reinforced with diagonal bars, were fabricated and tested under cyclic loading. The results show that the control specimen fails with plastic hinges formed at the beam-joint interfaces, while all other specimens fail with relocated plastic hinges on the beams. The two BCJ specimens reinforced with bonded and debonded diagonal bars show similar improvement over the control specimen in terms of joint damage level, loading capacity, energy dissipation, stiffness degradation, and bonding condition of beam longitudinal reinforcement. For instance, the BCJ specimens reinforced with bonded and debonded diagonal bars possess 9% and 12% higher loading capacity, and 13% and 7% higher energy dissipation than the control specimen. Debonding the diagonal bars can slightly reduce joint cracks but has marginal effect on the overall performance of BCJs. In addition, the debonding treatment weakens the contribution of the diagonal bars to joint shear resistance, as evidenced by the increased strain in joint stirrups. Furthermore, increasing the diameter of debonded diagonal bars enhances the ductility and energy dissipation of the BCJ specimens since this improves their buckling resistance after concrete spalling. In addition, finite element models for BCJs were developed and validated for parametric study. The simulation results indicate that insufficient diagonal bars can lead to unsuccessful relocation of plastic hinges in BCJs, which decreases the loading capacity and accelerates the load degradation. With similar total sectional area, reducing the number of diagonal bars deteriorates their anchorage in beams. This consequently weakens the flexural capacity at beam ends, leading to unsuccessful plastic hinge relocation and poor seismic performance of BCJs.